How is the Transparency of Zakat Management Entities in Indonesia? - Efri Syamsul Bahri; Halimah Yumna Zakiyyah; Ahmad Bisyri (IAIN Syekh Nurjati Cirebon, 2021)
Zakat is the third pillar of Islam. Zakat must meet the requirements of meeting the nisab. The potential for zakat in Indonesia reaches IDR 233.8 trillion, but its realization has only reached IDR 10.2 trillion. This study aims to measure the transparency index of zakat management entities in three dimensions: financial transparency, management, and programs. This study quantitatively measured using a descriptive approach. Data were collected through questionnaires from zakat management entities, namely Dompet Dhuafa, Indonesian Zakat Initiative, and Baitulmaal Muamalat. The data were processed using a multistage weight index model. A non-probability sampling approach with purposive sampling was used for the sample selection. This study indicates that the transparency index values of the three LAZs are in the transparent category. The Indonesian Zakat Initiative (n=0.90), Baitulmaal Muamalat (n=0.85), and Dompet Dhuafa (n=0.83). Initiative Zakat Indonesia (IZI) obtained the highest index value in the financial dimension. Baitulmaal Muamalat obtained the highest index value in the financial dimension. Dompet Dhuafa obtained the highest index value in the management dimension. Thus, the three LAZs must continue to maintain and increase the value of the transparency index to maintain a good zakat management entity